2022
DOI: 10.1039/d2cp01671k
|View full text |Cite
|
Sign up to set email alerts
|

Sulfuric acid–dimethylamine particle formation enhanced by functional organic acids: an integrated experimental and theoretical study

Abstract: Atmospheric new particle formation (NPF), which has been observed globally in clean and polluted environments, is an important source of boundary-layer aerosol particles and cloud condensation nuclei, but the fundamental...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 103 publications
(146 reference statements)
0
1
0
Order By: Relevance
“…40 Most recently, we explored the role of functional organic acids, ranging from monocarboxylic acid to dicarboxylic acids with hydroxyl groups, in NPF by turbulent flow tube experiment, and found that the enhancement to nucleation by dicarboxylic acids increases with hydroxyl group addition, indicating that tartaric acid (TA) with two hydroxyl groups may play an more important role in the initial nucleation steps of NPF. 41 However, most of these studies treated the clusters without the consideration of hydration and the competition between dicarboxylic acid and the nucleation precursor in the formation of pre-nucleation clusters remains to be investigated. Because water vapor (W) is ubiquitously present in the atmosphere at 8-10 orders of magnitude higher concentrations (10 16 -10 17 molecules cm À3 ) than other condensable gases, 42 the hydration effect on aerosol nucleation is significant.…”
Section: Introductionmentioning
confidence: 99%
“…40 Most recently, we explored the role of functional organic acids, ranging from monocarboxylic acid to dicarboxylic acids with hydroxyl groups, in NPF by turbulent flow tube experiment, and found that the enhancement to nucleation by dicarboxylic acids increases with hydroxyl group addition, indicating that tartaric acid (TA) with two hydroxyl groups may play an more important role in the initial nucleation steps of NPF. 41 However, most of these studies treated the clusters without the consideration of hydration and the competition between dicarboxylic acid and the nucleation precursor in the formation of pre-nucleation clusters remains to be investigated. Because water vapor (W) is ubiquitously present in the atmosphere at 8-10 orders of magnitude higher concentrations (10 16 -10 17 molecules cm À3 ) than other condensable gases, 42 the hydration effect on aerosol nucleation is significant.…”
Section: Introductionmentioning
confidence: 99%